Creation of preventive mass evacuation plan with the use of public transport - Teichmann, Dusan; Dorda, Michal; Soušek, Radovan (Elsevier Science BV, 2021)
The article deals with the planning of the preventive evacuation processes from the point of view of ensuring the mass transportation of inhabitants from hazardous areas, when dangerous substances that are leaking into the surroundings from factories and other industrial facilities (such as nuclear power plants) threaten the inhabitants. The approach presented in this article is based on multi-criteria mixed integer linear programming. Optimisation modelling has not been yet applied in the Czech Republic to create evacuation plans. The main contribution of the article lies in a new type of optimisation approach to evacuation planning when speed of the mass evacuation process is determinative. The mathematical model was applied to the planning of the mass evacuation process in the emergency planning zone which is demarcated around the nuclear power plant Dukovany in the Czech Republic.
Plánování hromadné plošné evakuace osob veřejnou dopravou.
Keywords: planning; preventive evacuation; linear programming; multicriteria optimisation; plánování; evakuace; lineární programování; krizové situace